An examination of the pull and push factors influencing hotel selection by Chinese outbound travelers. Issue 1 (2nd April 2016) - Mccartney, Glenn; Ge, ZhuYing
Abstract: This research examines what push and pull decision-making factors had significant influence in Macao hotel selection by Chinese guests. This is particularly important given Macao's present challenging hospitality competitive climate with several thousand new luxury hotel rooms by 2017 coupled with a decline in complimentary rooms required by casinos due to the reverse in Macao's gaming fortunes since 2014. Macao's casino and hospitality success since its Handover in 1999 has become increasingly reliant on Chinese visitation and particularly VIP casino patrons. With the luxury hotel segment benefiting from a complimentary casino room allotment, the crackdown by the Chinese leadership on corruption in 2014, which negatively impacted VIP casino play, means the acquisition of new Chinese leisure and business travel markets will be needed coupled with greater insight on their room purchase behaviour. As a cross-border location from Zhuhai where the hotel industry has flourished, Macao's luxury brand sector needs to appeal to a Chinese visitor who is historically and predominantly a day-tripper to Macao. Importantly, this study examined and found significant profile and travel behaviour differences with regard to push and pull factors influencing Macao hotel purchase by Chinese visitors. Most were repeat visitors to Macao booking rooms via intermediates rather than the hotel directly. Key important push and pull decision-making factors were found within certain traveller profiles, revealing areas requiring strategic focus for Macao hotel marketing initiatives and campaigns given this increasingly competitive landscape.